The Perilaku dan Aktor Politik dalam Kemenangan Kotak Kosong di Delapan Desa pada Pilkada Wonosobo 2020 - Detty Arimbi Hartas; Kushandajani; Dewi Erowati (PERSPEKTIF, 2023)
This study aims to determine political behavior and political actors in winning empty squares in eight villages in Wonosobo District in the 2020 Wonosobo Regional Head Election (Pilkada). The research method used in this research is a qualitative research method with a descriptive approach. The theory used in this research is the theory of political behavior and the theory of political actors. From the research conducted, it is known that the winning of empty squares in the eight villages was caused by several factors, namely (1) voters did not know a single candidate pair, (2) voters were apathetic towards election results, (3) voters did not like a single candidate pair, (4) voters want leaders from bureaucrats, (5) the existence of political actors in the form of empty box volunteers and members of the DPRD Wonosobo Regency.